What is the mechanism of government green development behavior considering multi-agent interaction? a meta-analysis - Li, Xingwei; Dai, Jiachi; Zhu, Xiaowen; He, Jinrong; Li, Jingru; Liu, Xiang; Huang, Yicheng; Shen, Qiong (MDPI, 2022)
Worsening environmental problems have created more and more challenges for green development, and the government is often seen as an important guide in turning this situation around. A government generally enacts green development through green development behavior, but previous research has not revealed the mechanism of this behavior. In addition, the multi-agent interaction between the government and green development behavior also needs to be explored. Based on an integrated theoretical model, the authors of this study adopted a meta-analysis method to analyze 18 high-quality published pieces from 6 mainstream databases and described the mechanism of government green development behavior in exploring and thinking about multi-agent interactions. In addition, the authors of this study explored differences in the roles of central and local government green development behaviors and the moderating role of regional heterogeneity. The research results showed that: (1) Enterprise economic behavior, enterprise environmental behavior, enterprise social behavior, and public participation are all significantly positively affected by government green development behavior; (2) local government green development actions have stronger effects than central government actions; (3) regional heterogeneity moderates the effect of government green development behavior. Furthermore, the authors of this study propose relevant countermeasures and suggestions from the government’s point of view. This research provides a theoretical and practical reference for governments to better improve their environmental systems and environmental supervision.
Keywords: government; green development; environmental regulation; government supervision; multi-agent; meta-analysis